Pengaruh Kualitas Produk, Kualitas Pelayanan, dan Harga Terhadap Kepuasan Pelanggan Pada Usaha Fotocopy 66 di Bumi Sani Bekasi Timur - Denis Putra Ramadhan; Andrian; Haryudi Anas (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The Effect of Product Quality, Service Quality, and Price on Customer Satisfaction at Photocopy 66 Business in Bumi Sani, East Bekasi.This study aims to determine how the relationship between the variables of Product Quality (X1), Service Quality (X2), and Price (X3) on Customer Satisfaction at Photocopy 66 in Bumi Sani, East Bekasi. The research data is data taken using a questionnaire using a google form distributed to customers who have come more than 3 times to Fotocopy 66 Bumi Sani East Bekasi. The population in this study is unknown and the sample in this study was 100 customers determined using the Hair formula. The data analysis used is the classical assumption test and multiple linear regression analysis, to test and prove the research hypothesis using the SPSS version 26 application